Promosi Media Sosial dalam Meningkatkan Citra Positif dan Kuantitas Peserta Didik MTs Al-Amiriyyah Blokagung Banyuwangi - Ahmad Faqih Badrul Murtaja; Dewi Lyien Ien (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was conducted because the researchers' interest in the development of academic achievement and the quantity of students at MTs Al-Amiriyyah Blokagung was quite rapid, to analyze what kind of promotions were used by WKS Public Relations in increasing the positive image and quantity of students at MTs Al-Amiriyyah Blokagung and to analyze what factors -Factors that can affect the positive image and quantity of students owned by MTs Al-Amiriyyah Blokagung.The approach used in this study is a qualitative approach with a descriptive type of research. The method used in data collection is Observation related to social media promotion in increasing the positive image and quantity of students. Interviews with the Principal, WKS Public Relations and Media Team, as well as documentation data and archives of activities from the management at MTs Al-Amiriyyah Blokagung. The researcher uses the Miles and Huberman model, namely reduction, presentation and conclusion drawing or data verification. The results of the research obtained from the field stated that the image and quantity owned by MTs Al-Amiriyyah Blokagung in the eyes of the community was considered good. The communication strategies used, such as maintaining communication patterns, planning and arranging tasks as WKS Public Relations at MTs Al-Amiriyyah Blokagung, as well as maintaining openness and information provided to the public can affect the image and quantity of MTs Al-Amiriyyah Blokagung. Based on this, it can be seen that the factors that affect the positive image and quantity of MTs Al-Amiriyyah Blokagung are by planning and carrying out the programs well, improving the service system, maintaining good communication and cooperation among members/teachers or with the community as well as the existence of disclosure of information to the public.